Language Style of Humour on Stand-Up Comedy Video - Merry Rullyanti; Nurdianto Nurdianto (Literary Criticism, 2019)
This study aims to identify and analyze the language styles and their characteristics in a stand-up comedy video. The data were taken from the stand-up comedy video and were collected by applying documentation method and note-taking techniques. The technique of analyzing data was done by giving the description and explanation of language style and characteristics. The data were analyzed by applying the theory of language style by Tannen (1990) and the characteristic of language by Coates (2004). The findings showed that all of language styles proposed by Tannen (1990) found in Pitch Perfect movies, those are: support, intimacy, understanding, feelings, proposal, and compromise. The characteristics of language found in the movies were to show a connote triviality, to get response on something, to show uncertainty, to give a suggestion, and to express feelings. Keyword: language style, stand-up comedy, characters